1979
DOI: 10.1104/pp.64.6.1039
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Citrate-stimulated Starch Synthesis Catalyzed by Starch Synthase I of Developing Maize Kernels

Abstract: Chromtography of extracts of maize on diethylaminoethyl-celllose resolvestarc synthae avity into two frcio (Ozbum, Hawker, Preiss 1971 Plant Physlo 4& 785-769). Only starc synthase I is capble of synthesis in the absece of added primer and the presene of 0.5 molar citrate. is enzym fratio has been purified about 1,000fold frm maize kernels for the eosrmnuitant amykAw-exseder (ae). Previous reports have shown glycogen and starch synthase fractions from a number of sources catalyze a-glucan synthesis in the abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

1981
1981
2004
2004

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(27 citation statements)
references
References 11 publications
(17 reference statements)
1
26
0
Order By: Relevance
“…Additional evidence exists for functional interactions between starch biosynthetic enzymes. In maize kernel extracts, the activity of SSI was greatly stimulated by the addition of purified SBEI or SBEII (Boyer and Preiss, 1979). Recently, Seo et al (2002) showed that functional interactions exist between heterologously expressed SBEs from maize and yeast glycogen synthases working in a cyclically interdependent fashion, which is consistent with the idea that starch metabolizing enzymes may function in protein complexes.…”
Section: ª 2004 American Society Of Plant Biologistssupporting
confidence: 66%
“…Additional evidence exists for functional interactions between starch biosynthetic enzymes. In maize kernel extracts, the activity of SSI was greatly stimulated by the addition of purified SBEI or SBEII (Boyer and Preiss, 1979). Recently, Seo et al (2002) showed that functional interactions exist between heterologously expressed SBEs from maize and yeast glycogen synthases working in a cyclically interdependent fashion, which is consistent with the idea that starch metabolizing enzymes may function in protein complexes.…”
Section: ª 2004 American Society Of Plant Biologistssupporting
confidence: 66%
“…In contrast, unprimed soluble starch synthase activity is totally dependent on high amounts of sodium citrate or sodium malate in in vitro experiments (3,12,20,23,25). In case of potato, at least 0.4 M sodium citrate was necessary to stimulate the unprimed soluble starch synthase activity in vitro (Fig.…”
Section: Unprimed Soluble Starch Synthase Activity Depends On High Ammentioning
confidence: 99%
“…Sodium dithionite (0.2% w/v) and DTT (1 mM), often used to stabilize the soluble starch synthases (3,12,25), had no effect on ADP-Glc incorporation into tissue slices (Fig. 1, lanes E and F).…”
Section: Incorporation Of Adp-gic Into Potato Tuber Slicesmentioning
confidence: 99%
See 2 more Smart Citations